Aspects of the biology and preliminary assessment of DNA quality and quantity of two cichlids from Lagos Lagoon, Nigeria - Olufemi O. Soyinka; Mutiu O. Sifau; Peace I. Adamu (Syiah Kuala University, 2022)
Aspects of the growth pattern, reproductive biology, and molecular characteristics of two cichlids, Sarotherodon melanotheron and Coptodon zillii were investigated in Lagos Lagoon. A total of twenty-nine individual species were collected from the Lagos Lagoon. Blood samples were obtained for DNA extraction and analysis from 9 specimens of each species. The morphometric data of S. melanotheron varied from 2.5-4.5cm (head length), 13.5-18.0cm (total length) and 35.00-135.00g (body weight), while that of C. zillii were 2.0-4.5cm, 12.0-21.5cm and 39.00-228.00g respectively. The growth pattern of S. melanotheron showed a positive allometric, b= 3.324, while that of C. zillii showed a negative allometric pattern with b= 2.715. The condition factors of S. melanotheron and C. zillii ranged from 4.15-4.55 and 4.12-5.07 respectively. The sex ratio for S. melanotheron was 1: 0.18, while C. zillii had a sex ratio of 1:0.33, and these were statistically significant (p 0.05). From the molecular characterization analysis, the DNA concentration ranged from 48-1265ng/µl and DNA purity ranged from 1.49-1.82. These findings form baseline information for conducting further investigations on the taxonomy, ecology, conservation of the genetic purity of these fisheries resources in Lagos Lagoon.